Engineering Tube Casting Machine of Organic Planting Pouch - Pudjiono, Ekoyanto; Ahmad, Ary Musthofa; Subekti, Rachman (Jurnal Teknologi Pertanian, 2001)
Problem in using polybag for the seed container is the necessity of seed replacement into field that still uses cutting or tearing method of polybag. Unfortunately, the methods cause to rooting damages or the root will be sheared. Koesriharti (1987) reports that seed dying often occurs after replacement, or the growth will be prohibited for the rooting system have been failed. Other problem in using polybag is waste consideration, because polybag composites of polyester. An alternative to reduce plastic matters is by decreasing the use of polybag. Nowadays, the use and research on planting pouch from organic substance are developed. Instead of less dangerous to environment and cheaper, it increases humus desired by plants. One material of organic planting pouch is enceng gondok. Because it contains high fiber and undesirable plants, they should be usable waste. Machine casting the planting pouch is expected to change dry enceng pieces into tube shapes. The process involves pressing and rolling the dry pieces by roll mechanism. Research is conducted from April to September 2001 in TSSU and Agriculture Laboratory of Machine and Capacity. Casting machine designed comprises to frame, hopper, calendar roll, strip roll, coil roll, capacity sustaining mechanism, and power source. Machine experiment has been conducted by involving enceng pages in 0,5 mm thickness and 50 mm width. Tube result by D = 40 mm indicates that machine performance capacity is about 1,2 m / hours and its productivity is 435,9 mm. Financial analysis based on initial investment as much as Rp. 550.000 obtains BT value for Rp. 143.913 per year, while BV for Rp. 6.789.600 per year. BEP value is Rp. 211.351,316 in product capacity of 44,8253 m/year. NPV value isÂ  Rp. 48.370.560,13. Net B/C Ratio to 88,94 and IRR to 75,45 % is also observed with selling price for Rp. 4.715 per meters. Â  Keywords: tearing method, organic planting pouch, tube casting machine